Diagnosis and Treatment of Syncope - Youichi Kobayashi, MD (Journal of Arrhythmia, 2006)
Accurate diagnosis of syncope is essential because it ranges from cardiac syncope with a very poor prognosis to neurally-mediated syncope (NMS) with a relatively favorable prognosis. Diagnosis of syncope, however, is difficult in many patients even by HUT, so a new loading method for HUT or implanted Holter ECG monitoring will be required in the future. The prognosis of NMS itself may be favorable, but it may cause the aggravation of complications.